A Review Paper on Analytical Study on the Structure Behaviour of Regular and Irregular Space Frame Bystaad.Prov8i (International Journal of Engineering Management Science, 2023)
A procedure of optimizing a space truss only by varying the geometric shape of the truss and keeping the cross section of the element kept constant. The shape variations will be done on the basis of raising the height. The maximum deflection produced in the structure, weight of steel required by the structure and percentage of failed member has been considered as measured. Optimization is a process of subjecting all members present in the structure to minimum usage thereby ensuring the utilization ratio of each and every element more than 80%. It is to be noted that the structural properties not be compromised. The structure has to be made of limit state design and should be simply supported roof. Space truss design in the technique for assigning a structure using skeleton- type approach, as opposed to traditional piece -by - piece or ground- up construction. Irrespective of advantage of the structure economical efficiently of structure3 decides success of it. Hence the space truss will be designed and optimized during our project. The shape will be varied for the best result and optimized shape is to be determined.
Keywords: Symmetric and asymmetric Structure, Building Analysis, Storey Displacement, Base Shear, Storey Drift, STAAD-Pro v8i